Synthesis and characterization of monophosphinic acid DOTA derivative: A smart tool with functionalities for multimodal imaging - Chilla, Satya Narayana Murthy; Zemek, Ondrej; Kotek, Jan; Boutry, Sébastien; Larbanoix, Lionel; Sclavons, Coralie; Elst, Luce Vander; Lukes, Ivan; Muller, Robert N; Laurent, Sophie (Bioorganic & medicinal chemistry, 2017)
A new facile synthetic strategy was developed to prepare bifunctional monophosphinic acid Ln-DOTA derivatives, Gd-DO2AGAP(NBn) and Gd- DO2AGAP(ABn). The relaxivities of the Gd-complexes are enhanced compared to Gd-DOTA. Monophosphinic acid arm of these Gd-complexes affords enhancement of inner sphere water exchange rate due to its steric bulkiness. The different functionalities of DO2AGAP(NBn) were appended in trans positions and are designed to conjugate identical or different vectors according to the potential applications. The conjugation of Gd-DO2AGAP(ABn) with E3 peptide known to target apoptosis was successfully performed and in vivo MRI allowed cell death detection in a mouse model.
Keywords: Animals; Heterocyclic Compounds, 1-Ring; Magnetic Resonance Imaging; vztah mezi dávkou a účinkem léčiva; Female; Multimodal Imaging; ženské pohlaví; Molecular Structure; Structure-Activity Relationship; Mice; magnetická rezonanční tomografie; myši; heterocyklické sloučeniny monocyklické; molekulární struktura; Dose-Response Relationship, Drug; kontrastní látky; vztahy mezi strukturou a aktivitou; multimodální zobrazování; zvířata; Contrast Media